Implementing the Eclectic Blend of Genre-Based Instruction, Cooperative Learning, and Gamification to Improve Students’ Knowledge of Songs - Azizah, Sarah Nur; Anita Triastuti (Universitas Negeri Yogyakarta, 2025)
Enhancing students' understanding of figurative language in English song lyrics presents a significant challenge in English Language Teaching (ELT). This research explored the collective impact of integrating Genre-Based Instruction (GBI), Cooperative Learning, and Gamification on improving students' knowledge and understanding of songs. The integration of modern approaches such as Genre-Based Instruction (GBI) in English Language Teaching (ELT) has significantly enhanced students' linguistic and communicative competencies. GBI encourages students to consider audience, purpose, and context, which is particularly beneficial in understanding complex language forms such as figurative language. The study aimed to assess how this eclectic blend influenced students' comprehension of figurative language, as well as their linguistic competence, critical thinking, and creativity. The research utilized a Classroom Action Research (CAR) design with both qualitative and quantitative methods. The study involved 36 students from a public school in Ngaglik, Sleman, Yogyakarta, and their English teacher, who also served as the homeroom teacher. Data collection included qualitative methods such as classroom observations, interviews, and documentation, as well as quantitative data from pre-tests, cycle 1 tests, and cycle 2 tests (post-tests). Qualitative data were analyzed through data condensation, data display, and conclusion drawing, while quantitative data were processed and analyzed similarly. The results of qualitative and quantitative analysis, along with triangulation, indicate a significant improvement in students' ability to understand and use figurative language. The combined use of GBI, cooperative learning, and gamification proved effective in creating a dynamic learning environment that enhances students' comprehension of figurative language in songs. The integration of GBI provided a structured framework for analyzing various song genres, while cooperative learning created a collaborative environment that fostered deeper engagement with the material. The gamification element introduced a competitive and enjoyable aspect that increased student motivation and participation. However, challenges such as varying student proficiency levels and the need for additional support were noted. Future research should explore the long-term effects of these strategies on overall language skills, address diverse student needs, and evaluate various gamification techniques. These insights will help refine the application of these methods in diverse educational contexts.